Estimating soil water content in a thorny forest ecosystem by time-lapse electrical resistivity tomography (ERT) and HYDRUS 2D/3D simulations - Faúndez Urbina, Carlos A.; Cabrera Alanís, Daniel.; Ramírez, Elizabeth; Seguel, Oscar; Fustos, Ivo J.; Díaz Donoso, Pablo.; Honorio de Miranda, Jarbas.; Rakonjac, Nikola; Elgueta Palma, Sebastián Andrés.; Galleguillos, Mauricio (John Wiley and Sons, 2023)
Determination of soil volumetric water content (Figure presented.) in forest ecosystems is particularly challenging due to deep rooting systems and unknown soil vertical and spatial heterogeneity. This research aims to test two undisturbed methods, electrical resistivity tomography (ERT) and HYDRUS 2D/3D, for 2D (Figure presented.) determination in a thorny forest ecosystem. The experiment consisted of infiltrating 10 L of water lasting 60 min. During infiltration, ERT measured apparent resistivity by time-lapse measurements, and (Figure presented.) was measured with an FDR probe (EnviroSCAN) at 33, 63, 83, 97, and 163 cm depth close to the infiltration site. At the end of infiltration, a soil pit was dug, and 100 measurements of (Figure presented.) were performed with a TDR in a 10 × 10 cm regular grid. Archie law transformed soil resistivity (ERT) into (Figure presented.) using manual calibration, verified by an independent dataset. The 2D (Figure presented.) profile obtained by ERT was qualitatively compared with the HYDRUS 2D/3D one. HYDRUS 2D/3D was parametrized with calibrated parameters obtained with HYDRUS 1D using 106 days of (Figure presented.) obtained with EnviroSCAN. The results of HYDRUS 1D calibration and verification were satisfactory, with RMSE and Nash-Sutcliffe coefficients ranging from 0.021 to 0.034 cm3 cm−3 and 0.11 to 0.77, respectively. The forward HYDRUS 2D/3D (Figure presented.) simulation disagrees with EnviroSCAN data for 33 cm depth. However, it follows the trend with near to zero variation of water content at 63 cm depth. Water content determination by ERT was satisfactory with RMSE for calibration and verification of 0.017 and 0.021 cm3 cm−3. HYDRUS 2D/3D and ERT comparisons were not equal, with a shallower wetting front by ERT and a deeper one for HYDRUS. Still, both wetting fronts agree with the wetting depth estimated by EnviroSCAN. We conclude that both methods are an alternative for (Figure presented.) determination in heterogeneous and deep soils of forest ecosystems.
Keywords: Applied geophysics; HYDRUS 1D; Vachellia caven; Water balance; Water transfer models